2002
DOI: 10.1100/tsw.2002.181
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Radionuclides in Surface Soils of Vietnam

Abstract: A database on U, Th, K, and Cs in surface soils was established to provide inputs for the assessment of the collective dose to the population of Vietnam and to support soil erosion studies using Cs as a tracer. A total of 292 soil samples was taken from undisturbed sites across the territory and the concentrations of radionuclides were determined by gamma spectrometry method. The multiple regression of Cs inventories against characteristics of sampling locations allowed us to establish the distribution of Cs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
Order By: Relevance
“…The estimated dose rate for farm soil and Nile island's soil are comparable with the results in China (Ziqiang et al, 1988), Vietnam (Hien et al, 2002), Yugoslavia (Bikit et al, 2005) and Brazil (Malanca et al, 1993).…”
Section: Calculation Of Radiological Effectssupporting
confidence: 78%
“…The estimated dose rate for farm soil and Nile island's soil are comparable with the results in China (Ziqiang et al, 1988), Vietnam (Hien et al, 2002), Yugoslavia (Bikit et al, 2005) and Brazil (Malanca et al, 1993).…”
Section: Calculation Of Radiological Effectssupporting
confidence: 78%
“…The contents of natural radionuclides in the soil are very important because these radionuclides contribute significantly to the collective dose of the general population 11 . Some researchers have measured activity concentrations of natural radionuclides in soil in Vietnam 12 14 . The most recent observations 13 for all of Vietnam showed that the average concentrations of 238 U, 232 Th and 40 K were 43 ± 18 Bq kg −1 , 60 ± 20 Bq kg −1 and 442 ± 230 Bq kg −1 , respectively, which are 1.2, 2.0 and 1.0 times higher than the worldwide averages 1 .…”
Section: Introductionmentioning
confidence: 99%